Preparing Maps for Distribution of Pollutant Concentrations of Shatt Al-Arab Water - A. Hassan, Wassan; Shamikh Zageer, Dheaa; S. Mohamed, Nadira; F. Khanjer, Ebtesam; M. , Almayyhi; B. , Almayahi (International Journal of Psychosocial Rehabilitation, 2020)
Due to the importance of water and its necessity, it is considered one of the most important topics of interest to scientists and specialists in the field of pollution. In this study, water pollution in the Shatt al-Arab for the month of March 2015 data were used for five monitoring stations in the Shatt al-Arab (SH1, SH2, SH3, SH4, and SH5) and several pollutants. The study used methods of mathematical induction in the GIS program. Analytical maps of the distribution and distribution of contaminants in the Shatt al-Arab.